A systematic review of pharmacoeconomic evaluations on oral diarylquinoline-based treatment for drug-resistant tuberculosis: from high to low burden countries. (3rd September 2021) - Fekadu, Ginenus; Yao, Jiaqi; You, Joyce H.S.
ABSTRACT: Introduction : There is a rising global interest in the pharmacoeconomic evaluations of bedaquiline (BDQ), a novel oral diarylquinoline, for treatment of drug-resistant tuberculosis (DR-TB). Areas covered : This article systematically reviewed publications retrieved from Medline, American Psychological Association-Psychology information, Web of Science, Embase, Scopus, Science direct, Center for Reviews and Dissemination, and CINAHL Complete during 2010–2020 on pharmacoeconomic studies on BDQ for DR-TB treatment. Ten Markov model-based cost-effectiveness analyses identified were conducted in high (n = 4), intermediate (n = 2), and low (n = 4) TB burden countries. Expert opinion : The paucity of model-based health economic analyses on BDQ-containing regimens for DR-TB indicated that further pharmacoeconomic research of BDQ-based regimens, on the aspects of duration of BDQ treatment, types of DR-TB indicated, and settings of regions and health-systems, is highly warranted to inform global cost-effective use of BDQ-based regimens for DR-TB treatment.